2011
DOI: 10.1177/1062860611415391
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Quality Improvement Training Course

Abstract: This study assessed the effectiveness of Quality Academy Teams Training, a team-based process improvement program at Mayo Clinic. The study population consisted of employees who attended the course in 2008 (n = 103). A pretest-posttest design was used to assess learning by participants of the course, and gain score analysis was conducted using paired t test procedures. Electronic surveys were sent to participants 90 days following completion of the course to assess self-reported application of skills and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…QI programme relevance rating (10). Self-efficacy and willingness to conduct a future QI project (9) Management support (12) and availability of resources (13) Project outcome metrics (17) Ruud et al 29 QI project as part of QI training (1). Programme developed in partnership (4) Transfer of knowledge and skills gained back to the work setting (7) Kirkpatrick model, 21 including 'learning' and 'behaviour' (9) Ng and Trimnell 30 QI project as part of QI training (1).…”
Section: Evaluations Of Roi In Qi Initiativesmentioning
confidence: 99%
“…QI programme relevance rating (10). Self-efficacy and willingness to conduct a future QI project (9) Management support (12) and availability of resources (13) Project outcome metrics (17) Ruud et al 29 QI project as part of QI training (1). Programme developed in partnership (4) Transfer of knowledge and skills gained back to the work setting (7) Kirkpatrick model, 21 including 'learning' and 'behaviour' (9) Ng and Trimnell 30 QI project as part of QI training (1).…”
Section: Evaluations Of Roi In Qi Initiativesmentioning
confidence: 99%
“…Schuchter, Rutt, Satariano and Seto (2015) relied on interviews and asked about knowledge before and after training to measure trainees' learning. Ruud et al (2012) used a preexperimental pretest-posttest design with paper-and-pencil tests to assess learning improvements. The results indicated that the participants gained knowledge as a result from the training program.…”
Section: Learning Assessmentmentioning
confidence: 99%
“…No que diz respeito ao desenho de pesquisa, nos estudos estrangeiros, percebe-se maior equilíbrio entre a utilização dos diversos desenhos. Também nas pesquisas estrangeiras, verifica-se que a maior parte dos estudos é transversal, embora tenham sido encontrados oito estudos longitudinais (Tan et al, 2003;Gaudine & Saks, 2004;Cromwell & Kolb, 2004;Saks & Belcourt, 2006;Steensma & Groeneveld, 2010;Dalston & Turner, 2011;Reupert et al, 2012;Ruud et al 2012).…”
Section: Resumo Das Pesquisas Estrangeiras Sobre Avaliação De Treinamunclassified
“…Houve predomínio do uso de questionários, porém, também foram encontrados grupo focal, entrevista, roteiro para análise documental e observação direta em complementação à entrevista. Dentre os questionários aplicados, verificam-se teste de aprendizagem com aplicação antes e após o treinamento (Laing & Andrews, 2011;Reupert et al, 2012;Ruud et al, 2012), teste situacional (Liu, Grandon & Ash, 2009) Analisa-se que a agenda é ampla e envolve inclusão de variáveis a serem investigadas, níveis de avaliação e questões metodológicas, assim como a agenda brasileira. O que mais chama a atenção nas duas agendas são as sugestões metodológicas, que envolvem realização de experimentos ou quase-experimentos, utilização de grupos de comparação e utilização de múltiplas fontes e dados objetivos.…”
Section: Resumo Das Pesquisas Estrangeiras Sobre Avaliação De Treinamunclassified
See 1 more Smart Citation